Receipt of high-frequency ventilation is associated with acute kidney injury in very preterm neonates - Haynes, Nicholas; Bell, Jeremiah; Griffin, Russel; Askenazi, David J.; Jetton, Jennifer; Kent, Alison L. (Pediatric nephrology (Berlin, West), 2024)
Background High-frequency ventilation (HFV) is frequently used in critically ill preterm neonates. We aimed to determine the incidence of acute kidney injury (AKI) in neonates less than 29 weeks gestation who received HFV in the first week of life and to determine if the rates of AKI differed in those who received other forms of respiratory support. Methods This retrospective cohort study of 24 international, level III/IV neonatal intensive care units (NICUs) included neonates less than 29 weeks gestation from the AWAKEN study database. Exclusion criteria included the following: no intravenous fluids ≥ 48 h, admission ≥ 14 days of life, congenital heart disease requiring surgical repair at < 7 days of life, lethal chromosomal anomaly, death within 48 h, severe congenital kidney abnormalities, inability to determine AKI status, insufficient data on ventilation, and when the diagnosis of early AKI was unable to be made. Subjects were grouped into three groups based on ventilation modes (CPAP/no ventilation, conventional ventilation, and HFV). Results The incidence of AKI was highest in the CPAP/no ventilation group, followed by HFV, followed by conventional ventilation (CPAP/no ventilation 48.5% vs. HFV 42.6% vs. conventional ventilation 28.4% ( p = 0.009). An increased risk for AKI was found for those on HFV compared to CPAP/no ventilation (HR = 2.65; 95% CI:1.22–5.73). Conclusions HFV is associated with AKI in the first week of life. Neonates on HFV should be screened for AKI. The reasons for this association are not clear. Further studies should evaluate the relationship between ventilator strategies and AKI in premature neonates. Graphical abstract A higher resolution version of the Graphical abstract is available as Supplementary information